Topographic traversing of high accuracy inside the campus of Universidad del Qu (2019)
This article describes the design procedure, monumentation and measuring system traversing inside the campus of Universidad del Quindío, with classical instruments, which is used as a framework to support the surveying and mapping work of the institution, under technical requirements to support their relative and absolute precision through coordinates determined on the horizontal reference system for Colombia: Datum MAGNA-SIRGAS. The methodology was structured under the theory of errors, defining the limit of the uncertainties expected in terms of the technical characteristics of measuring instruments, the geometry of the polygon, and designs of measurement methods. Interesting findings were obtained in terms of error propagation and ellipses, because of their magnitudes, shapes and orientations defined the direction of strengthening the geometric framework.